2015
DOI: 10.1111/jcpp.12469
|View full text |Cite
|
Sign up to set email alerts
|

Annual Research Review: Sleep problems in childhood psychiatric disorders – a review of the latest science

Abstract: Hippocrates flagged the value of sleep for good health. Nonetheless, historically, researchers with an interest in developmental psychopathology have largely ignored a possible role for atypical sleep. Recently, however, there has been a surge of interest in this area, perhaps reflecting increased evidence that disturbed or insufficient sleep can result in poor functioning in numerous domains. This review outlines what is known about sleep in the psychiatric diagnoses most relevant to children and for which as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(200 citation statements)
references
References 264 publications
(327 reference statements)
8
180
1
3
Order By: Relevance
“…Fourth, early-life stress has been linked to alcohol and substance abuse disorders and smoking (Dube et al, 2003;Anda et al, 1999), which can increase inflammation levels (Crews et al, 2006;Shiels et al, 2014). Fifth, early-life stress has been associated with decreased total sleep and disruption in sleep architecture in rodents (Feng et al, 2007;Mrdalj et al, 2013;Tiba et al, 2004) and humans (Gregory and Sadeh, 2016;Kajeepeta et al, 2015). In turn, clinical experiments have shown that sleep deprivation is associated with an increase in the expression of pro-inflammatory cytokines in humans (Irwin et al, 2006), and epidemiological studies have found that reduced sleep is associated with elevated levels of inflammation biomarkers (Miller et al, 2009).…”
Section: Brain Developmentmentioning
confidence: 99%
“…Fourth, early-life stress has been linked to alcohol and substance abuse disorders and smoking (Dube et al, 2003;Anda et al, 1999), which can increase inflammation levels (Crews et al, 2006;Shiels et al, 2014). Fifth, early-life stress has been associated with decreased total sleep and disruption in sleep architecture in rodents (Feng et al, 2007;Mrdalj et al, 2013;Tiba et al, 2004) and humans (Gregory and Sadeh, 2016;Kajeepeta et al, 2015). In turn, clinical experiments have shown that sleep deprivation is associated with an increase in the expression of pro-inflammatory cytokines in humans (Irwin et al, 2006), and epidemiological studies have found that reduced sleep is associated with elevated levels of inflammation biomarkers (Miller et al, 2009).…”
Section: Brain Developmentmentioning
confidence: 99%
“…Therefore, we cannot ignore the sleep difficulties that these children have and we must reflect about the relationships between this general sleep poor quality and other types of behaviour and disturbances. As Gregory & Sadeh (2016) write, it is increasingly evident that childhood sleep disturbances are predictors of a wide range of psychopathologies and behavioural problems, although some associations are little known and are yet to be explored.…”
Section: Resultsmentioning
confidence: 99%
“…The practice guidelines 50 of the American Academy of Child and Adolescent Psychiatry emphasize the need to address the safety and efficacy of these medications with preschoolers, especially considering the developing brain of young children. Medications are justified primarily to treat comorbid symptoms among children 51 , for example sleeping problems 49,52 .…”
Section: Journal Of Mental Health and Clinical Psychologymentioning
confidence: 99%